Strengthening the Character of Sportsmanship and Cooperation in Football Games (Department of Physical Education, Sport, Health and Recreation, 2023)
Character development in students can begin at an early age. Many character characteristics such as sportsmanship and cooperation are taught in physical education. The purpose of this study was to identify strengthening sportsmanship and cooperation in football learning. This research includes action research related to football learning. The subjects of the study were 15 students of high school 14 Luwu, Bonelemo Village, West Bajo Regency. This research uses 4 stages of design which include the stages of planning, action and observation, reflection, after completion of reflection. Through research design, it can determine the improvement of sportsmanship and cooperation in football defense. This study focuses on the design of action research which includes (1) behavioral aspects in students by 70%. (2) Psychomotor performance tests with an average score of at least 70% in the good category. The results showed that in cycle 1 the character of sportsmanship was 47% and cycle 2 was 80%. While the character of cooperation in cycle 1 is 48% and cycle 2 is 82%. The conclusion is that the strengthening of character from the pre-cycle stage, cycle 1 and cycle 2 shows that the importance of the role of an educator in cultivating the value of sportsmanship and cooperation. Student character develops as a result of supportive learning environments, interactive learning settings, and student collaboration and good sportsmanship with each other while learning. Strengthening the characteristics of sportsmanship and cooperation can be implemented in conscious continuous football learning and instilling habits in students.